2016
DOI: 10.1007/s00572-016-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional analysis of two phosphate transporter genes from Rhizopogon luteolus and Leucocortinarius bulbiger, two ectomycorrhizal fungi of Pinus tabulaeformis

Abstract: Inorganic phosphorus (Pi) is essential for plant growth, and phosphate (P) deficiency is a primary limiting factor in Pinus tabulaeformis development in northern China. P acquisition in mycorrhizal plants is highly dependent on the activities of phosphate transporters of their root-associated fungi. In the current study, two phosphate transporter genes, RlPT and LbPT, were isolated from Rhizopogon luteolus and Leucocortinarius bulbiger, respectively, two ectomycorrhizal fungi forming symbiotic interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…a). Such a role in Pi uptake has already been ascribed to HcPT2 (Tatry et al ., ) as well as for other H + :Pi symporters whose proteins or transcripts were detected in ECM (Garcia et al ., ; Wang et al ., ; Zheng et al ., ) or arbuscular mycorrhizal (AM) (Harrison & van Buuren, ; Xie et al ., ) fungi. The fact that transgenic lines overexpressing HcPT2 were unaffected in their Pi uptake could be due to a saturation of the Pi transport in nonlimiting Pi concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a). Such a role in Pi uptake has already been ascribed to HcPT2 (Tatry et al ., ) as well as for other H + :Pi symporters whose proteins or transcripts were detected in ECM (Garcia et al ., ; Wang et al ., ; Zheng et al ., ) or arbuscular mycorrhizal (AM) (Harrison & van Buuren, ; Xie et al ., ) fungi. The fact that transgenic lines overexpressing HcPT2 were unaffected in their Pi uptake could be due to a saturation of the Pi transport in nonlimiting Pi concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The search for homologous genes in available genomes of ECM fungi shows that the vast majority of Basidiomycete species display only H + :Pi symporters, contrary to the Ascomycete Tuber melanosporum, which harbors both Pi:Na + and H + :Pi symporters (Casieri et al, 2013;Hacquard et al, 2013;Nehls & Plassard, 2018). To date, only two P transporters from Hebeloma cylindrosporum (HcPT1.1 and HcPT2), one from Boletus edulis (BePT), one from Rhizopogon luteolus (RlPT) and one from Leucocortinarius bulbiger (LbPT) have been characterized as high-affinity H + :Pi transporters (Tatry et al, 2009;Wang et al, 2014;Zheng et al, 2016). Recent analysis of the H. cylindrosporum genome revealed another putative H + :Pi transporter closely related to HcPT1.1 and called HcPT1.2 (Casieri et al, 2013;Kohler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to HcPT1.1, upregulation by low Pi has been found for other H + /Pi transporters in Tricholoma spp. (Kothe et al., 2002), Boletus edulis (Wang, Li, et al., 2014; Wang, Yu, et al., 2014), Rhizopogon luteolus (Zheng et al., 2016), and Leucocortinarius bulbiger (Zheng et al., 2016).…”
Section: Consistent Role Of Mycorrhizas and Root Exudates In Phosphor...mentioning
confidence: 99%
“…Liu et al (2015) found that drought stress upregulated the level of R. intraradices and soybean mitogen-activated protein kinase (MAPK) transcripts in mycorrhizal soybean roots, indicating the possibility of a molecular dialogue between AM fungus and host plant and suggesting that they might cooperate to improve soybean’s resistance to drought stress. Concurrently, in terms of nutrient absorption, some studies investigated the mycorrhiza-regulated phosphate transporters in host plants Astragalus sinicus (Xie et al 2013), Oryza sativa (Sun et al 2012), P. tabulaeformis (Zheng et al 2016a), pepper and tobacco (Chen et al 2007), and reciprocal transportation of carbon and phosphorus amongst plants ( Zea mays and Medicago sativa ), Rhizophagus irregularis and phosphate-solubilising bacterium (Zhang et al 2016; Wang et al 2016a). Wang et al (2014) demonstrated that H + -ATPase played a key role in energising the periarbuscular membrane, thereby facilitating nutrient exchange in arbusculated rice and Medicago truncatula cells.…”
Section: Molecular Biology Of Mycorrhizal Fungimentioning
confidence: 99%